Forest genetic resources: IPGRI's strategic action plan - International Plant Genetic Resources Institute (2000)
The conservation and use of forest genetic resources is one of eight priority domains of IPGRI's strategy. The specific goal of I P G R I 's FGR programme is to ensure the continuous availability of these resources for present and future use, through in situ and ex situ measures that allow species adaptation and evolution to changing environments. The scope and complexity of challenges to be addressed by the FGR programme require the development of a strategic framework, which ensures the optimum use of limited resources to maximize the impact of specific actions. Therefore IPGRI's FGR programme focuses on two major areas: - Strengthening institutional frameworks and contributing to international collaboration and policy-making; - Generating knowledge and developing appropriate methodologies and tools for conservation and use of forest genetic resources.